KATEKESE DENGAN METODE BERBASIS MEDIA VISUAL MEMBANGUN SIKAP MENGAMPUNI ANGGOTA KOMUNITAS TULI EFATA - Leo, Bernadeth Lidya; Dadi, Kanisius Komsiah (CREDENDUM: Jurnal Pendidikan Agama, 2025)
Recognising the unique needs of Deaf friends, who often struggle with sensory, communication, behavioural, and activity constraints, is crucial. In interaction, conflicts arising from misunderstandings may occur, which lead to various negative emotions such as anger, hatred, silence, avoidance, gossip, and dissatisfaction. This study addresses the challenge of fostering a forgiving attitude among Efata’s community members through effective visual-based catechesis. Using images, dramas, videos, and sign language, this method is more effective in conveying a message of forgiveness. This research uses qualitative methods with data collection techniques such as interviews, observations, and literary studies. The subject of the investigation is a friend of Tuli in the Rawamangun Parish community. Based on the investigation obtained data that Tuli Efata's community members do not understand the meaning of the attitude of forgiveness. Through the visual-based catechesis, Tuli's friends are easier to understand, feel, and be inspired, and otivated through visual media such as video, images, inspiring and meaningful forgiveness. Keywords: Deaf PD, forgiveness, visual methods.